Detection of viral SARS‐CoV‐2 genomes and histopathological changes in endomyocardial biopsies. (12th June 2020) - Escher, Felicitas; Pietsch, Heiko; Aleshcheva, Ganna; Bock, Thomas; Baumeier, Christian; Elsaesser, Albrecht; Wenzel, Philip; Hamm, Christian; Westenfeld, Ralph; Schultheiss, Maximilian; Gross, Ulrich; Morawietz, Lars; et al.
Abstract: Aims: Since December 2019, the novel coronavirus SARS‐CoV‐2 has spread rapidly throughout China and keeps the world in suspense. Cardiovascular complications with myocarditis and embolism due to COVID‐19 have been reported. SARS‐CoV‐2 genome detection in the heart muscle has not been demonstrated so far, and the underlying pathophysiological mechanisms remain to be investigated. Methods and results: Endomyocardial biopsies (EMBs) of 104 patients (mean age: 57.90 ± 16.37 years; left ventricular ejection fraction: 33.7 ± 14.6%, sex: n  = 79 male/25 female) with suspected myocarditis or unexplained heart failure were analysed. EMB analysis included histology, immunohistochemistry, and detection of SARS‐CoV‐2 genomes by real‐time reverse transcription polymerase chain reaction in the IKDT Berlin, Germany. Among 104 EMBs investigated, five were confirmed with SARS‐CoV‐2 infected by reverse real‐time transcriptase polymerase chain reaction. We describe patients of different history of symptoms and time duration. Additionally, we investigated histopathological changes in myocardial tissue showing that the inflammatory process in EMBs seemed to permeate vascular wall leading to small arterial obliteration and damage. Conclusions: This is the first report that established the evidence of SARS‐CoV‐2 genomes detection in EMBs. In these patients, myocardial injury ischaemia may play a role, which could explain the ubiquitous troponin increases. EMB‐based identification of the cause of myocardial injury may contribute to explain the different evolution of complicated SARS‐CoV‐2‐infection and to design future specific and personalized treatment strategies.